The UN Charter is our rules! Interview with Anna M. Evstigneeva, Deputy Permanent Representative of the Russian Federation to the United Nations - Anna M. Evstigneeva (Vestnik RUDN. International Relations, 2023)
The practice of the functioning of the United Nations and the actual mechanisms of peacekeeping differ significantly from the theoretical ideas about them. Anna Mikhailovna Evstigneeva, Deputy Permanent Representative of the Russian Federation to the United Nations (UN), who has been dealing with peacekeeping issues for many years, answers a number of important questions about contemporary peacekeeping and peacebuilding in her interview. She argues that while the West is building a “rules-based order,” for Russia the rules are the UN Charter. The key to ensuring the effectiveness of an international organization, according to A.M. Evstigneeva, is the ability of the parties to reach mutually beneficial solutions and to take each other’s interests into account. The rest is a “superstructure,” which, however, is partially enshrined in the doctrine. Dozens of factors (dialogue with civil society, gender, climate, etc.) play a special role, which over time become universal. Often, the beautiful Western theories of liberal peacebuilding do not stand up to the harsh reality; and in a number of cases there is silence on the part of decision-makers about the real situation on the ground. This interview highlights the challenges of the existing system of international peacekeeping in the context of the formation of a multipolar world.